DIVERSIFIKASI OLAHAN CUMI KERING “CUMKRING O500” DI DESA OLIMOO’O KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO - Femy M Sahami; Sri Nuryatin Hamzah (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
Olimoo’o village as a coastal village has abundant squid potential, so the group of women conducted the processing of dried squid products which are named "Cumkring O500". The problem that arises over time is that the business does not work as expected. The Community Empowerment Learning (KKN PPM) Real Work Lecture Program directs students to apply their knowledge to maximise community empowerment to develop the cumkring potential to become a superior product of the village which leads to an increase in the community's economy. Through this program the transfer of dried squid processing technology is carried out which aims to improve group skills in processing to product marketing, creating diversification of processed dried squid ready and improving the economy of the community. The method used is the active involvement of all group members through group learning techniques accompanied by mentoring and direct practice at all stages of the process. The output of this activity is an increase in group knowledge about the processing of dried squid, the creation of processed squid products with three levels of flavour, namely original, selow and hot issue and product socialisation. The long-term target of this activity is the Cumkring O500 product to become an icon of Olimoo’o Village, as expected by the government and society. Therefore, there needs to be a commitment from the group in cumkring processed innovation and group strengthening to create a sustainable production house, and develop it into Micro, Small, and Medium Enterprises (MSMEs) as a form of independence, equitable economic growth, and increasing community income.